Nematode diversity in banana rhizosphere from northern districts of Bangladesh - Abedin, Noynul; Ara, Nuzhat; Ali, M Sohrab; Khalequzzaman, M (Journal of Bio-Science, 2012)
Context: Banana is one of the most important fruits crops among the different fruit crops in the agricultural and its intensively cultivated in all over the parts of Bangladesh especially in northern part. Many species of plant parasitic nematodes are association with banana root systems and are mainly responsible for controlling the banana productions to greater extend. Objective: Keeping in view of the disturbing nature of the nematode pest, the present study was undertaken to examine the biodiversity of plant parasitic nematodes associated with banana intensively grown in northern districts of Bangladesh. Materials and Methods: The collection of nematodes was conducted in the banana growing areas of Bogra, Natore, Rajshahi, Rangpur and Gaibandha districts. In each area, banana fields of different commercial cultivars were chosen for collection of soil and root samples. From each field 10 plants were selected randomly for sample collection. Each subsample consisted about 1 kg of soil and 20 g of fleshy roots taken from a single mat from a depth of 10-30 cm and from three equidistant points (40-50 cm) around the pseudostem Nematodes were extracted from soil by Cobbs sieving technique and from root by Mechanical maceration technique, and processed by Seinhorsts slow dehydration method. Fixing was done in boiling lactophenol cotton blue and finally by formalin glycerin solution. Dehydrated nematodes were kept in glycerol-ethanol solution and mounted permanently on glass slides. Identification was done up to species following the keys. Results: Among the plant parasitic nematodes ten species belonging to nine genera, six families of a single order, viz. Helicotylenchus dihystera, Rotylenchulus reniformis, Meloidogyne incognita, Hoplolaimus galeatus, Tylenchorhynchus mashhoodi, Tylenchorhynchus annulatus, Criconemoides sp., Hemicriconemoides cocophillus, Cephalenchus emarginatus and Aphelenchus avenae were encountered. Among the non-parasitic nematodes 15 genera belonging to seven families and three orders viz. Acrobeles, Acrobeloides, Aporcelaimus, Aporcelaimium, Aporcelaimellus, Cephalobus, Dorylaimus, Dorylaimoides, Discolaimus, Discolaimium, Discolaimoides, Indodorylaimus, Mylonchulus, Iotonchus, and Rhabditis were found to be associated with soils in banana field. It was found that species H. galeatus, C. emarginatus and M. incognita were present in all the surveyed areas. Four species of parasitic nematodes viz. C. emarginatus, H. cocophillus, Criconemoides sp. and A. avenae and 5 genera of non parasitic nematodes viz., Aporcelaimium, Aporcelaimellus, Discolaimium, Discolaimoides and Indodorylaimus are reported for the first time in Bangladesh. Conclusion: Present investigation have clearly indicated that the association of plant parasitic nematodes especially the most an important nematodes species like Hoplolaimus galeatus, Cephalenchus emarginatus and Meloidogyne incognita would cause severe economic yield loss to banana plantation in the study area. DOI: http://dx.doi.org/10.3329/jbs.v19i0.13003 J. bio-sci. 19 65-75, 2011